Late Byzantine Cherson according to Archaeological Data: For the Question whether This City Existed in the Late-thirteenth and Fourteenth Century - Nataliia Vitalievna Ginkut (Античная древность и средние века)
This article examines the archaeological finds from the last quarter of the thirteenth and fourteenth century, which shed light on the history of mediaeval Chersonese (Cherson). After the catastrophe that Cherson experienced in the third quarter of the thirteenth century, the urban settlement continued existing. The arguments are the living rooms and the graves in former churches and cemeteries that survived in some areas of the ancient city. However, the size of the city and the number of townsfolk drastically decreased, and life did not revive in some areas (the north-eastern, northern, and partially western). In the first half of the fourteenth century, Cherson did active commerce, as it comes from the finds of imported pottery and Golden Horde coins. In the middle and the second half of the fourteenth century, material culture of the local population showed a relatively high material level: the archaeological layers contained the pottery imported from Byzantine, Italian, and Golden Horde centres, and the excavations of the graves uncovered fragments of expansive textiles embroidered with silver and gold. All these circumstances allow the one to interpret the late-thirteenth and fourteenth century Cherson as a small port town included into the Genoese trade system in the Crimea.